Some Biochemical Parameters of Pisum sativum Extracted with Lactobacillus lactis - Nilay Güvenç, Ayse; Kirbag, Sevda (Asian Journal of Chemistry, 2013)
This study analyzed the effects of inulin containing Pisum sativum on Lactobacillus lactis. In the study, fatty acid, flavonoid, resveratrol content, vitamin, phytosterol levels and the antimicrobial activities of P. sativum and the fatty acid, flavonoid, resveratrol content, vitamin, phytosterol levels and antimicrobial activities of L. lactis extracts treated with P. sativum were determined and compared. For this purpose, the control (P. sativum), L. lactis treated with P. sativum (Ps+Ll) and L. lactis only cultures (Ll) were used. According to experimental results the fatty acid and vitamin levels of the P. sativum extracts significantly increased after being treated with L. lactis significantly increased whereas in the controls that the flavonoid and resveratrol levels decreased while the antimicrobial activity showed variations.